การจำลองซีเอฟดีของฟลูอิไดซ์เบดแก๊ส-ของแข็งสำหรับอนุภาคผสม - ธเนศพล ตั้งพัฒนธนา (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Gas-solid fluidized beds have widely used in various industrial applications due to many advantages of the technology such as excellent gas-solid particle contacting, which then has a good effect on mass and heat transfers. The purposes of this study were to investigate a CFD model for mixed particles in a two-dimensional fluidized bed system and analyze the effect of operating parameters on heat transfer in the system by using ANOVA. In addition, the mixing parameters including radial-dispersion coefficient, axial-dispersion coefficient, granular temperature and mixing index were compared. The results showed that EMMS model was relatively consistent with the experiment than the other models. The effect of operating parameters on mixing between coal and sand showed that inlet gas velocity, sand diameter, coal diameter and initial sand height were statistically significant on heat transfer coefficient. Furthermore, the effect of adding coal dust into system on the hydrodynamics was studied. The fluidization behavior was higher when coal dust was added. Both coal dust diameter and inventory were statistically significant to heat transfer. A comparison of mixing parameters, based on the assumption that good heat transfer is resulting from good mixing, showed that granular temperature gave relatively similar trend to heat transfer more than the other parameters. However, the relation between granular temperature and heat transfer is just a basic relationship. In other word, if granular temperature trend is known, the heat transfer trend is predicted.